Arm to leg coordination in elite butterfly swimmers - Chollet, D.; Seifert, L.; Boulesteix, L.; Carter, M. (International Journal of Sports Medicine, 2006)
This study proposed the use of four time gaps to assess arm-to-leg coordination in the butterfly stroke at increasing race paces. Fourteen elite male swimmers swam at four velocities corresponding to the appropriate paces for, respectively, the 400-m, 200-m, 100-m, and 50-m events. The different stroke phases of the arm and leg were identified by video analysis and then used to calculate four time gaps (T1: time gap between entry of the hands in the water and the high break-even point of the first undulation; T2: time gap between the beginning of the hands' backward movement and the low break-even point of the first undulation; T3: time gap between the hands' arrival in a vertical plane to the shoulders and the high break-even point of the second undulation; T4: time gap between the hands' release from the water and the low break-even point of the second undulation), the values of which described the changing relationship of arm to leg movements over an entire stroke cycle. With increases in pace, elite swimmers increased the stroke rate, the relative duration of the arm pull, the recovery and the first downward movement of the legs, and decreased the stroke length, the relative duration of the arm catch phase and the body glide with arms forward (measured by T2), until continuity in the propulsive actions was achieved. Whatever the paces, the T1, T3, and T4 values were close to zero and revealed a high degree of synchronisation at key motor points of the arm and leg actions. This new method to assess butterfly coordination could facilitate learning and coaching by situating the place of the leg undulation in relation with the arm stroke.